Drug Testing for Newborn Exposure to Illicit Substances in Pregnancy: Pitfalls and Pearls - Karen J. Farst; Jimmie L. Valentine; R. Whit Hall (International Journal of Pediatrics)
Estimates of the prevalence of drug usage during pregnancy vary by region and survey tool used. Clinicians providing care to newborns should be equipped to recognize a newborn who has been exposed to illicit drugs during pregnancy by the effects the exposure might cause at the time of delivery and/or by drug testing of the newborn. The purpose of this paper is to provide an overview of the literature and assess the clinical role of drug testing in the newborn. Accurate recognition of a newborn whose mother has used illicit drugs in pregnancy cannot only impact decisions for healthcare in the nursery around the time of delivery, but can also provide a key opportunity to assess the mother for needed services. While drug use in pregnancy is not an independent predictor of the mother's ability to provide a safe and nurturing environment for her newborn, other issues that often cooccur in the life of a mother with a substance abuse disorder raise concerns for the safety of the discharge environment and should be assessed. Healthcare providers in these roles should advocate for unbiased and effective treatment services for affected families.